The Management of Production/Services Unit in Business and Marketing Expertise Program in State Vocational High School 2 Singkawang - Gunanto Gunanto (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2018)
A school’s production/services unit (P/SU) constitutes a process of business activity for both academic and commercial purpose that the school performs continuously by empowering the school’s members and environment in the form of professionally-managed production/ services business unit.This research aims at 1) describing the planning of production/services unit in Business and Marketing Expertise Program at State Vocational High School 2 Singkawang, 2) describing the organization of production/services unit in Business and Marketing Expertise Program at State Vocational High School 2 Singkawang, 3) describing the operation of production/services unit in Business and Marketing Expertise Program at State Vocational High School 2 Singkawang, 4) describing the monitoring of production/services unit in Business and Marketing Expertise Program at State Vocational High School 2 Singkawang, 5) describing the obstacles encountered in managing the production/services unit in Business and Marketing Expertise Program at State Vocational High School 2 Singkawang, 6) describing the efforts made to deal with these obstacles encountered in managing the production/services unit in Business and Marketing Expertise Program at State Vocational High School 2 Singkawang.                The approach in this research is qualitative strengthened with descriptive method. The research focus is on the management of production/services unit in Business and Marketing Expertise Program at State Vocational High School 2 Singkawang in such aspects as planning, operation, organization and monitoring. The data are gathered using interview, observation and documentation.The research findings are: 1) The planning of production/services unit in Business and Marketing Expertise Program at State Vocational High School 2 Singkawang takes the school’s vision and missions and its education and business aspects into consideration, 2) the organization begins with the establishment of administrators and drafting the main job descriptions and functions of each department in a clear and comprehensible language, 3) The field executors actively involved in the production unit’s activities as daily sales service officers are those selected students from the so-called Alfamart class which constitutes a cooperation between the school and PT. Sumber Alfaria Trijaya Tbk., 4) the presence of this Business and Marketing Expertise Program’s production unit has been capable of adding more places and increasing the capacity for apprentice or industrial work practice students,  5) the monitoring of production unit is performed towards officer’s behavior, customers, administration and good stock. Finally, 6) the more spacious room needs to be immediately selected based on the capacity and service duration in order to optimize the potential customers which amount to more than 1,200 students and teachers.